Different seed rates of forage maize with a fixed stand of cowpea affects proximate composition of both species - Barsila, S. R. (Journal of Agriculture and Forestry University, 2020)
Mixed cultivation of fodder maize (Zea mays) and cowpea (Vigna unguiculata) is popular due to their fast-growing, high biomass yielding, high palatable, and mutualistic growing behavior. Evaluation of status of chemical composition of these mixed stands grown with different seed rates of maize, but with a fixed stand of cowpea would suggest the best period of forage harvesting and also the appropriate seed rate. Accordingly an experiment was done by following standard agronomic practices to grow maize-cowpea at Agriculture and Forestry University (AFU) Rampur, Nepal during May to September 2016. The experiment was done by using randomized complete block design (RCBD) consisting of 4 treatments, T1 (40kg/ ha maize seed), T2 (50kg/ha maize seed), T3 (30kg/ha maize seed) and T4 (40kg/ha maize seed + weeding) along with 20 kg/ha of cowpea seed for each treatment, and 5 replications, under a similar rate of chemical fertilizer. Samples were tested for proximate analysis at Animal Nutrition laboratory of AFU. A highly significant result was obtained among different treatments for crude fibre, crude protein, and ash content while ether extract content was statistically similar among the treatments in both the harvests. Maximum ash (10.94%) and crude fibre (31.24%) content were obtained in T1 on maize stem, and higher crude protein (CP) (28.09%) content was obtained in T3 on cowpea that was similar with T2 on cowpea for CP content at 45 days after sowing. At 75 days after sowing, higher crude fibre (CF) (35.87%) content was obtained for treatment T4 on maize stem. Research results suggested that harvesting of maize is suitable at 45 days after sowing (DAS) if higher ash and crude fibre requirement for balanced feed is expected to meet by using 40 kg seed rate of maize/ha whereas harvesting of cowpea at 75 DAS would be more appropriate if highest crude protein content is expected to harvest, but it would be possible to attain at the cost of higher crude fiber content. Nevertheless results clearly indicated that inclusion of fodder cowpea as a legume component in a fodder stand, such as maize could be helpful for a persistent nutritive value during later stage of harvesting.